Algoritma Dijkstra dan Bellman-Ford dalam Sistem Pemetaan Barbershop di Kota Lhokseumawe - Rozzi Kesuma Dinata; Bustami Bustami; Ar Razi; Muhammad Arasyi (INFORMAL: Informatics Journal, 2022)
A Barbershop service provider is a company that provides hair care to the community. Many people are currently doing business in this field, and many business actors are opening Barbershops in a variety of locations, ranging from campuses to office districts to densely populated towns. In Lhokseumawe City, there are 12 Barbershops. The application's benefit is that it can identify the shortest path from the user's location to the selected Barbershop, as well as the Barbershop's location and a brief description of the Barbershops in Lhokseumawe City. Only the system's defined nodes can be used to find the fastest route to the Barbershop. Dijkstra's method was chosen because it works against all current alternative functions and provides the shortest path from all nodes, ensuring that the shortest path is produced optimally. Because the Bellman-Ford algorithm is a variant of the BFS (best-first-search) algorithm, which is also employed in the search for the closest distance when the search for the closest distance has a negative weight, it was chosen. The same results were obtained in picking the route based on the results of the route selection test. However, when the two techniques are compared in terms of program execution time, Dijkstra's algorithm is faster than the Bellman-Ford algorithm.